2021
DOI: 10.1371/journal.pone.0259839
|View full text |Cite
|
Sign up to set email alerts
|

Gender roles and intimate partner violence among female university students in Spain: A cross-sectional study

Abstract: Background Traditional gender roles (GRs) have a considerable influence on relationships among couples. These can lead to negative health effects in women; however, their impact on intimate partner violence (IPV) has been less explored, especially among younger women. Objective To explore the association between traditional GRs and several indicators of IPV on a sample of Spanish female university students involved in heterosexual dating relationships. Methods A cross-sectional study involving female unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…students, since at those ages, young people's first relationships usually begin or are consolidated (Llano-Suárez et al, 2021). Prevention and detection is also crucial in this context, since universities are institutions that promote health, ensure the right to the freedom, physical and emotional integrity of all its collective, and are guarantors of progress in our society (Spanish Network of Healthy Universities, 2021).…”
Section: Most Of These Instruments Have Been Validated In Young Unive...mentioning
confidence: 99%
See 1 more Smart Citation
“…students, since at those ages, young people's first relationships usually begin or are consolidated (Llano-Suárez et al, 2021). Prevention and detection is also crucial in this context, since universities are institutions that promote health, ensure the right to the freedom, physical and emotional integrity of all its collective, and are guarantors of progress in our society (Spanish Network of Healthy Universities, 2021).…”
Section: Most Of These Instruments Have Been Validated In Young Unive...mentioning
confidence: 99%
“…TDV‐VP Scale (Soriano et al, 2021), Dating Violence Questionnaire‐R (DVQ‐R; Rodríguez‐Díaz et al, 2017), Conflict in adolescent dating relationships inventory short form (CADRI‐S; Fernández et al, 2012) and the Conflict Tactics Scales (CTS) in its different versions, modified (CTS‐M; Ronzón et al, 2019) or revised (CTS‐2; Anderson & Leigh, 2011). Most of these instruments have been validated in young university students, since at those ages, young people's first relationships usually begin or are consolidated (Llano‐Suárez et al, 2021). Prevention and detection is also crucial in this context, since universities are institutions that promote health, ensure the right to the freedom, physical and emotional integrity of all its collective, and are guarantors of progress in our society (Spanish Network of Healthy Universities, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Anicama Queneche [31], Boira et al [32], and Casique [33] show that women who are victims of intimate partner violence are forced to have sex without a condom or do not have a say in the fnal decision of whether to use a condom or not, which is intrinsically related to our data. Llano-Suárez et al [34] used the Dating Violence Questionnaire-R (DVQ-R) aimed at university students in Spain and found that most of them were passive, submissive, coerced, and detached; they sufered humiliation and experienced sexual and physical violence by a dominant and aggressive partner. Te studies of Anitha and Lewis [15], Díaz Martínez [16], Diéguez Méndez et al [35], López Francés and Tapía [17], and Sharoni and Klocke [18] like ours established that training and education regarding dating violence is essential for both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are fundamental for planning prevention and intervention programs against dating violence in university environments, according to Alp Yilmaz and S ¸ener Taplak [25]. Llano-Suárez et al [34] also stated that universities should adopt policies about gender equality and raise awareness about dating violence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, academic emotional exhaustion, marked by feelings of burnout, fatigue, and disengagement from academic pursuits, is prevalent among students and can have detrimental effects on their academic performance and overall well-being (Kelmendi & Baumgartner, 2020). Studies have shown a bidirectional relationship between intimate partner violence and emotional exhaustion, with experiences of violence contributing to increased stress and decreased academic functioning, and academic stressors exacerbating the risk of intimate partner violence victimization or perpetration (Llano-Suárez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%